Engaging male partners in women's microbicide use: evidence from clinical trials and implications for future research and microbicide introduction. Issue 3 (8th September 2014) - Lanham, Michele; Wilcher, Rose; Montgomery, Elizabeth T; Pool, Robert; Schuler, Sidney; Lenzi, Rachel; Friedland, Barbara
Abstract : Introduction: Constructively engaging male partners in women‐centred health programs such as family planning and prevention of mother‐to‐child HIV transmission has resulted in both improved health outcomes and stronger relationships. Concerted efforts to engage men in microbicide use could make it easier for women to access and use microbicides in the future. This paper synthesizes findings from studies that investigated men's role in their partners' microbicide use during clinical trials to inform recommendations for male engagement in women's microbicide use. Methods: We conducted primary and secondary analyses of data from six qualitative studies implemented in conjunction with microbicide clinical trials in South Africa, Kenya, and Tanzania. The analyses included data from 535 interviews and 107 focus groups with trial participants, male partners, and community members to answer research questions on partner communication about microbicides, men's role in women's microbicide use, and potential strategies for engaging men in future microbicide introduction. We synthesized the findings across the studies and developed recommendations. Results: The majority of women in steady partnerships wanted agreement from their partners to use microbicides. Women used various strategies to obtain their agreement, including using the product for a while before telling their partners, giving men information gradually, and continuing to bring up microbicides until resistant partners acquiesced. Among men who were aware their partners were participating in a trial and using microbicides, involvement ranged from opposition to agreement/non‐interference to active support. Both men and women expressed a desire for men to have access to information about microbicides and to be able to talk with a healthcare provider about microbicides. Conclusions: We recommend counselling women on whether and how to involve their partners including strategies for gaining partner approval; providing couples' counselling on microbicides so men have the opportunity to talk with providers; and targeting men with community education and mass media to increase their awareness and acceptance of microbicides. These strategies should be tested in microbicide trials, open‐label studies, and demonstration projects to identify effective male engagement approaches to include in eventual microbicide introduction. Efforts to engage men must take care not to diminish women's agency to decide whether to use the product and inform their partners.